Achieving Food System Resilience Requires Challenging Dominant Land Property Regimes - Calo, Adam; McKee, Annie; Perrin, Coline; Gasselin, Pierre; McGreevy, Steven; Sippel, Sarah Ruth; Desmarais, Annette Aurélie; Shields, Kirsteen; Baysse-Lainé, Adrien; Magnan, André; Beingessner, Naomi; Kobayashi, Mai (Frontiers in Sustainable Food Systems, 2021)
Although evidence continues to indicate an urgent need to transition food systems towards agroecological production, there is little sign of significant policy commitment towards food system transformation in global North geographies. The authors, a consortium of researchers studying the land-food nexus argue that a key lock-in explaining the lack of reform arises from how most food system interventions work through dominant logics of property to achieve their goals of agroecological production. Doing so fails to recognize how land tenure systems, codified by law and performed by society, construct agricultural land use. The authors argue that achieving food system resilience requires urgent attention to the underlying property norms that drive land access regimes, especially where norms of property appear hegemonic. This paper first reviews research from political ecology, critical property law, and human geography to show how property relations in the global North frustrate the advancement of alternative models like agroecology, and mediate acceptable forms of “sustainable agriculture”. Drawing on emerging cases of land tenure reform from the authors’ collective experience working in Scotland, France, Australia, Canada and Japan, we next observe how contesting dominant logics of property creates space to forge deep and equitable food system transformation. Equally, these cases demonstrate how powerful actors in the food system leverage legal and cultural norms of property to legitimize their control over the resources that drive agricultural production. We suggests that visions for food system resilience must embrace the reform of property relations as much as it does diversified farming practices.